Success Factors of Automobile After-Sales Services in China - Alexander Fraß; Christopher Zerres (Hochschule Offenburg, Fakultät Medien, 2016)
Automobile premium brands operate globally, which is undoubtedly required, because, for the most part, domestic markets are either decreasing or stagnating. China has become today the most important and biggest car market. Recently selling has become challenging because urban areas are well penetrated, and in poorly penetrated rural areas, incomes are low. This is particularly alarming for German brands, because of their premium orientation. Simultaneously, the after-sales market in China has been growing continuously. As a result, this market has a huge potential, which is likewise attractive because it has been scientifically proven across industries that after-sales services are high-margin profit drivers. Despite its great significance, the Chinese automobile after-sales market remains insufficiently researched, especially in terms of critical success factors and cultural influences, which therefore was the starting point for a study. The results will presented and interpreted now in this new working-paper.
urn:nbn:de:bsz:ofb1-opus4-50268
Keywords: 650